Application of the Sustainable Sites Initiative Rating System in Urban Green Space Construction in China—The Case of Xuhui Runway Park - Guangsi Lin; Xin Zhu; Xiaoqi He (Land, 2024)
The Sustainable Sites Initiative (SITES) is a comprehensive evaluation system for sustainable landscape, which has been promoted successfully and widely recognized in the landscape architecture industry. However, the existing research lacks attention to the applicability of SITES to urban green space construction projects in China. Therefore, exploring the application of the SITES evaluation system in the context of Chinese urban green space development is of great importance. Building upon theoretical research on sustainable landscapes, this study focuses on urban green space projects as the research carrier, with SITES as the subject of investigation. Utilizing the case study method, a thorough description and analysis of Xuhui Runway Park, a representative case officially certified by SITES in China, is provided. Across four stages—project initiation and planning, scheme design, construction, and operation—this study discusses the approaches employed in Chinese urban green space projects to meet the requirements of the SITES evaluation system. By evaluating the applicability of SITES to Chinese urban green space projects, identifying limitations in system promotion, and offering references for sustainable design practices, this study advances the application and promotion of SITES in China and contributes to the sustainable development of the landscape architecture industry.